Aspergillus Infections in Patients Received Lung Transplantation. (July 2018) - Chen, Wenhui; Qi, Yingjie; Chen, Jingyu; Guo, Lijuan; Liu, Yingmei; Liang, Chaoyang; Ma, Qianli; Wang, Chen
Abstract : Introduction: Lung transplantation recipients has a high susceptibility of fungal infection due to immunosuppression, allograft denervation, and impaired mucociliary clearance function. Fungal infection, especially aspergillus infection, is associated with all-cause mortality after lung transplantation. The aim of this study is to evaluate the incidence and clinical features of aspergillus infection following lung transplantation. Materials and Methods: A total of 47 patients with end-stage lung diseases received lung transplantation during March 2017 to November 2017 in China-Japan Friendship hospital. All patients received aerosolized Amphotericin B and injection of caspofungin for Prophylaxis therapy. Experienced physicians of pulmonary and critical care medicine made the diagnosis of infection. Aspergillus infection was defined as either a positive culture and pathological evidence of tissue invasion, or a elevated galactomannan level in blood or bronchoalveolar lavage fluid plus clinical findings supporting fungal infection. Results: There were 40 male recipients and 7 female recipients, age between 27-71 years old, median age was 62 years. 18 of the 47 (38.3%) lung transplantation recipients suffered from aspergillus infections. The most common infection type was aspergillus tracheobronchitis(AT), counting for 50.0% of all aspergillus infections. Invasive pulmonary aspergillosis(IPA) occurred in five patients(27.8%), three of which were combination with AT. Seven patients(38.9%) received experimental antifungal therapy because of a lack of conclusive evidence and they eventually considered aspergillus infections due to their exact efficacy. In etiology, aspergillus fumigatus was the most(55.6%), followed by aspergillus flavus(22.2%). It was worth mentioning that all bronchial stenosis, as a postoperative complication, occurred in patients with fungal infections in our lung transplantation center(five patients). Figure. No caption available. Figure. No caption available. Conclusions: Aspergillus infection has a high incidence in lung transplantation recipients. Much work need to be done in diagnosis and treatment of aspergillus infection.